The effects of replicative senescence and telomerase on contraction and motility of fibroblasts. - Peterson, Joanne Lykins (My University, 2009)
Fibroblasts are important in wound healing as they can create tension, migrate into a wound, and differentiate into myofibroblasts that produce a contractile force to close the wound. Replicative senescence, or the limit of the number of times a cell divides, may influence the ability of the fibroblast to heal the wound. This study was designed to investigate the formation of myofibroblasts, contraction ability and migration rate of three populations of cells derived from the same cell line: (1) those with early population doublings, (2) those with late population doublings, and (3) cells that can divide infinitely due to expression of telomerase (hTERT). A significantly higher percent of myofibroblasts was observed in hTERT cells (p < 0.001), and treatment with transforming growth factor-?1 produced significantly more myofibroblasts in all three cell ages (p<0.001) when cells were plated on coverslips that provided immediate tension. However, in an environment where tension was not immediate, but developed over time, myofibroblast formation and contraction was limited in all cell ages. Migration of fibroblasts was not significantly affected by cell age or presence of telomerase. The addition of telomerase increased myofibroblast formation, limited their contraction and had no effect on their migration, but may have increased proliferation rates. Overall, the results showed that replicative senescence did not have an effect on myofibroblast formation or migration, but could affect contraction rate.
Keywords: Myofibroblasts; Wounds and injuries; Cells; Telomerase; Wound healing